Are schools digitally inclusive for all? Profiles of school digital inclusion using PISA 2018. (September 2021) - Kim, Hye Jeong; Yi, Pilnam; Hong, Ji In
Abstract: This study used international student achievement data from the OECD's Programme for International Student Assessment (PISA) 2018 to identify the profiles of school digital inclusion (SDI). In digitally inclusive schools, students who live in the digital era benefit from digital technology and a digitally enhanced educational environment without alienation and exclusion. We compiled profiles of SDI by conducting a latent profile analysis on data from 27 countries. Multinomial logistic regression analyses were conducted to examine whether a school's socioeconomic status and type could predict its likelihood of fitting a particular profile across SDI subgroups. Schools were categorized in terms of low-, medium-, and high-level digital inclusion. Socioeconomic status and type of school were significant predictors of profile membership. Based on the results, the practical implications for promoting SDI include digital infrastructure as a prerequisite, teachers' confidence in using digital technology and instructional competence, and the digital skills of teachers and students. Highlights: School digital inclusion is a school's capability of ensuring students' educational experiences with digital technologies. We compiled profiles of school digital inclusion by conducting latent profile analysis using PISA 2018. Schools were categorized into low-, medium-, and high-level digital inclusion.